Les activités de conservation des lémuriens par le Groupe d’Etude et de Recherche sur les Primates de Madagascar (GERP) - Rose Marie Randrianarison; Hanta Razafindraibe; Jonah Ratsimbazafy; Fanantenana Rasolofoniriana Andriatsarafara; Lucien Marie Aimé Rakotozafy (Revue de Primatologie)
The Madagascar Primate Research Group (GERP - Groupe d’Etude et de Recherche sur les Primates de Madagascar) is a conservation-focused association created in 1994 by the initiative of researcher lecturers and students from the Department of Paleontology and Biological Anthropology and the Department of Animal Biology of the University of Antananarivo. The GERP membership consists of multidisciplinary scientists, both Malagasy and foreign, the majority of whom are primatologists. The principle actions of the association are focused on research on the prosimian primates of Madagascar, the development of action plans for their conservation, the discovery of new species, the translocation of lemurs living in deforested or threatened habitats, the abundance estimates and the revision of area distributions and the publication of results research in national and international scientific journals. In fact, capacity building of local community associations and primary and higher education systems concerning lemur conservation linked to aiding the sustainable development of local communities, it seems necessary, so that the lemur conservation will be lasting.